2017
DOI: 10.4028/www.scientific.net/ssp.264.120
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tensile Properties of Compatibilized and Uncompatibilized Low-Density Polyethylene/Jackfruit Seed Flour (LDPE/JFSF) Blends at Different JFSF Content

Abstract: Currently, natural fillers seem to be the suitable materials in polymer industry, which have emerged as a viable and abundant replacement for the relatively high-cost and non-renewable conventional fillers. However, the direct introduction of natural fillers into polymer matrix could effect negatively on some properties. Therefore, the aim of this work is to evaluate the influence of jackfruit seed flour (JFSF) (before and after compatibilization) on the tensile properties of (LDPE/JFSF) blends. Different JFSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It can be observed that there was little change in the dimension of sample EPDM/AF 15 , as shown in Figure 3. It is widely accepted that the swelling is directly related to the cross-linking density of molecular chains [39][40][41], and less solvent uptake or penetration into the blends indicated higher cross-linking density. However, there is no cross-linking reaction between EPDM molecular chains and AF fiber; the lower solvent uptake or penetration into the blends could be attributed to the AF fiber, which restricted the slippage between the polymer chains [41].…”
Section: Swelling Property Of Ceramifiable Epdm Compositesmentioning
confidence: 99%
“…It can be observed that there was little change in the dimension of sample EPDM/AF 15 , as shown in Figure 3. It is widely accepted that the swelling is directly related to the cross-linking density of molecular chains [39][40][41], and less solvent uptake or penetration into the blends indicated higher cross-linking density. However, there is no cross-linking reaction between EPDM molecular chains and AF fiber; the lower solvent uptake or penetration into the blends could be attributed to the AF fiber, which restricted the slippage between the polymer chains [41].…”
Section: Swelling Property Of Ceramifiable Epdm Compositesmentioning
confidence: 99%